2021
DOI: 10.3390/ani11041000
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lake Ecosystems on Mineral Concentrations in Tissues of Nile Tilapia (Oreochromis niloticus L.)

Abstract: This study evaluates the differences in mineral and toxic trace element concentrations of Nile tilapia (Oreochromis niloticus) tissues from three aquatic ecosystems in Ethiopia—Lake Ziway, Lake Langano, and Gilgel Gibe reservoir—with a focus on edible (fillet) and discarded (digestive tract, gills, skin, and liver) parts. A total of sixty (n = 60) Nile tilapia samples were collected, comprising twenty (n = 20) fish from each lake, and analyzed by inductively coupled plasma mass spectrometry. All elements varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
3
2
1
Order By: Relevance
“…Bayissa et al. ( 2021 ) reported that some macrominerals of Nile tilapia fish filet in dry bases in three different Ethiopia lakes that are 220–240 mg/100 g for Ca, 100–300 mg/kg for Na and 80–140 mg/100 g for Mg which is slightly agreed with the present result. Also, the Na and K content in Nile tilapia powder is agreed with 153.204 ± 2.99–207.182 ± 4.69 mg/100 g and 140.21 ± 8.00–186.16 mg/100 g in dry bases, respectively, as reported by Tsegay et al.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Bayissa et al. ( 2021 ) reported that some macrominerals of Nile tilapia fish filet in dry bases in three different Ethiopia lakes that are 220–240 mg/100 g for Ca, 100–300 mg/kg for Na and 80–140 mg/100 g for Mg which is slightly agreed with the present result. Also, the Na and K content in Nile tilapia powder is agreed with 153.204 ± 2.99–207.182 ± 4.69 mg/100 g and 140.21 ± 8.00–186.16 mg/100 g in dry bases, respectively, as reported by Tsegay et al.…”
Section: Resultssupporting
confidence: 91%
“…In this study, the iron content of OFSP and Nile tilapia fish powder have significant differences between their mean (p ≤ .05), and their result was 3.01 ± 0.03 and 18.82 ± 0.12 mg/100 g, respectively. The iron content of Nile tilapia fish powder was lower than 22.8-24.9 mg/100 g, which reported that the iron content of dried OFSP was 1.19-5.1 mg/100 g, which agreed with the present result (Bayissa et al, 2021;Nicanuru et al (2015)).…”
Section: Ta B L Esupporting
confidence: 91%
See 2 more Smart Citations
“…Description of the three lakes in this study. Fish samples from the three lakes were used in this study, and a summary of limnological information is given in (Table 5) 37,45 . Lake Ziway is located in the central Rift www.nature.com/scientificreports/ third-largest freshwater lake in the country.…”
Section: Methodsmentioning
confidence: 99%